Analysis of pragmatic items in an ESL online adaptive placement test - Carrió-Pastor, María Luisa; Martín Marchante, Beatriz (International Journal of English Studies, 2018)
The work at hand is part of a wider study the aim of which was to determine what kind of factors influence pragmatic failure in an online adaptive placement test taken by Spanish students in their first year at university. A preceding analysis (Carrió and Martín, 2016) showed the type of personal factors that caused the exam takers pragmatic failure according to their own perception. In this paper, we go deeper and search about what specific pragmatic categories the items more frequently failed in the test belong to, so that we can reach some conclusions about its content validity and state whether the pragmatics construct is underrepresented or not in this test.